Effectiveness of School Financial Monitoring System in Misuse of Education Budget - Wan, Markus; Batang, Samson; Abeh, Yohanes Andy; Wibawa, Radhitya; Mebang, Desi Natalia; Warman, Warman; Mulawarman, Widyatmike Gede; Fitriadi, Ahmad (Jurnal Riset Ilmu Pendidikan, 2025)
School financial supervision plays a crucial role in ensuring transparency and accountability in managing education budgets. This study aims to analyze the effectiveness of the school financial supervision system in Mahakam Ulu in preventing budget misappropriation and to identify the factors influencing its effectiveness. A qualitative approach with a case study method was employed in several schools in Mahakam Ulu. Data were collected through in-depth interviews, direct observations, and document analysis related to school financial management. The findings reveal that the financial supervision system in Mahakam Ulu schools still faces various challenges, both internal and external. Internal factors affecting the effectiveness of supervision include the limited financial management competencies of school principals and treasurers, as well as a lack of transparency in financial administration. Meanwhile, external factors such as a shortage of auditors, limited periodic supervision by relevant agencies, and geographical constraints also hinder the implementation of effective oversight. Although regulations have established financial supervision mechanisms, their implementation at the school level remains suboptimal, particularly in utilizing technology to enhance transparency and efficiency in financial management. This study recommends several strategies to improve the effectiveness of school financial supervision, including strengthening human resource capacity through more intensive training, optimizing digital systems for financial recording and reporting, and increasing the number of supervisory personnel to ensure more systematic and comprehensive oversight. Additionally, greater involvement of school committees and the community in financial oversight is necessary to enhance transparency and accountability in managing educational funds. By implementing more adaptive and technology-based policies, school financial supervision in Mahakam Ulu is expected to function more effectively and contribute to improving the quality of education in the region.